Scalable noninvasive amplicon-based precision sequencing (SNAPseq) for genetic diagnosis and screening of β-thalassemia and sickle cell disease using a next-generation sequencing platform - Gupta, Pragya; Arvinden, V. R.; Thakur, Priya; Bhoyar, Rahul C.; Saravanakumar, Vinodh; Gottumukkala, Narendra Varma; Goswami, Sangam Giri; Nafiz, Mehwish; Iyer, Aditya Ramdas; Vignesh, Harie; Soni, Rajat; Bhargava, Nupur; et al. (Frontiers in Molecular Biosciences, 2023)
β-hemoglobinopathies such as β-thalassemia (BT) and Sickle cell disease (SCD) are inherited monogenic blood disorders with significant global burden. Hence, early and affordable diagnosis can alleviate morbidity and reduce mortality given the lack of effective cure. Currently, Sanger sequencing is considered to be the gold standard genetic test for BT and SCD, but it has a very low throughput requiring multiple amplicons and more sequencing reactions to cover the entire HBB gene. To address this, we have demonstrated an extraction-free single amplicon-based approach for screening the entire β-globin gene with clinical samples using Scalable noninvasive ampliconbased precision sequencing (SNAPseq) assay catalyzing with next-generation sequencing (NGS).We optimized the assay using noninvasive buccal swab samples and simple finger prick blood for direct amplification with crude lysates. SNAPseq demonstrates high sensitivity and specificity, having a 100% agreement with Sanger sequencing. Furthermore, to facilitate seamless reporting, we have created a much simpler automated pipeline with comprehensive resources for pathogenic mutations in BT and SCD through data integration after systematic classification of variants according to ACMG & AMP guidelines. To the best of our knowledge, this is the first report of the NGS-based high throughput SNAPseq approach for the detection of both BT and SCD in a single assay with high sensitivity in an automated pipeline.